Supply chain management: a global aspect and practice at ACI (Advanced Chemical Industries) Limited - Abdullah, Syed Ikram (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.